Technology-Based Academic Supervision: A Teacher Development Strategy Towards AI Literacy - Tri Astrit Lusito; Dety Mulyanti (Journal of Innovative and Creativity, 2025)
The development of digital technology and artificial intelligence (AI) requires teachers to have higher technological literacy to adapt to changing educational paradigms. Technology-based academic supervision presents itself as a coaching strategy that not only monitors teacher performance but also enhances digital skills through the use of LMS, AI tools, and online supervision platforms. This study aims to analyze how technology-based academic supervision can improve teachers' AI literacy and identify the most effective coaching strategies. The research method used a descriptive qualitative approach through interviews, observation, and documentation, with data validity tested through triangulation of sources and methods. The results show that technology-based supervision strengthens teachers' ability to use AI for lesson planning, automated evaluation, student learning data analysis, and digital media development. Coaching strategies include AI training, assistance in developing AI-based lesson plans, digital media workshops, and the formation of learning communities. The discussion reveals that the main challenges lie in infrastructure readiness, variations in teachers' digital literacy, and resistance to change. However, technology-based supervision has been shown to increase teacher confidence and create a more adaptive digital culture in schools. In conclusion, technology-based academic supervision is an effective and sustainable approach to improving teachers' AI literacy and supporting learning transformation in the digital era.